Client-Centered Stakeholder Relationship Management: A Strategic Model for Medium Business and Corporate Banking Relationships - Mahanani, Sasanti Putri; Wulandari, Maulina Pia; Safitri, Reza; Sharipudin , Mohamad-Noor Salehhuddin (Graduate School Universitas Brawijaya, 2026)
Objective: Relationship management plays a critical role in corporate banking, particularly in maintaining long-term engagement with medium-sized businesses and corporate clients. However, many financial institutions face challenges sustaining these relationships due to the lack of a systematic, client-centered approach. This study proposes a Client-Centered Stakeholder Relationship Management (SRM) Model to improve client engagement through a four-phase framework: Engage and Attract Potential Clients, Insight-Driven Client Engagement, Relationship Strengthening and Service Delivery, and Value Co-Creation and Retention. Design/Methods/Approach: This study employs a qualitative methodology, drawing on insights from 16 Relationship Managers (RMs) at Bank Rakyat Indonesia (BRI), classified into junior and senior levels based on experience. Findings: Effective communication, trust-building, and service satisfaction function as core relational mechanisms that influence client retention. Specifically, junior RMs rely more on structured systems such as CRM tools, while senior RMs demonstrate adaptive, experience-based strategies that enable more tailored client engagement. The findings further show that SRM effectiveness depends on integrating analytical tools, relational competence, and organizational support systems, particularly in managing corporate clients with complex financial needs. Originality/Value: While the model is derived from a single institutional context, it offers transferable insights for banking institutions with similar organizational structures and market conditions. Practical/Policy implication: Practically, this study recommends developing hybrid training programs that combine data-driven analysis and relational skills, implementing structured mentoring between junior and senior RMs, and integrating continuous client feedback into engagement strategies. These findings contribute to operationalizing SRM in corporate banking by linking stakeholder theory with frontline relational practices. Keywords: Client engagement; client retention; corporate banking; relational competence; stakeholder relationship management JEL Classification: G21; M31; L14